Mars Science Laboratory 2012
DOI: 10.1007/978-1-4614-6339-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity’s Mars Hand Lens Imager (MAHLI) Investigation

Abstract: The fine-scale textures of rock surfaces reflect a complex interplay of geologic processes that include those related to rock formation, exposure, weathering, and erosion. Typically, such features are studied in two dimensions using forensic geological techniques from scales from those visible to the naked eye to those in a wider-area context. Rock surface metrology is an emergent technique in which extremely fine-scale textural information is measured in 3D using laboratory instruments. Here we describe its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 66 publications
2
120
0
Order By: Relevance
“…With the use of a beam splitter, a microscopic imager records images of the sample through the same objective lens, allowing for imaging of the laser spot on the sample. A three-axis translation stage is used for sample positioning, and focus stacking (a standard procedure used to extend depth of field [34]) is used to obtain focused images over the entire image area for real mineral samples with unprepared surfaces and high roughness.…”
Section: Experimental a Instrument Overviewmentioning
confidence: 99%
“…With the use of a beam splitter, a microscopic imager records images of the sample through the same objective lens, allowing for imaging of the laser spot on the sample. A three-axis translation stage is used for sample positioning, and focus stacking (a standard procedure used to extend depth of field [34]) is used to obtain focused images over the entire image area for real mineral samples with unprepared surfaces and high roughness.…”
Section: Experimental a Instrument Overviewmentioning
confidence: 99%
“…Curiosity landed in Gale Crater, Mars, in August 2012; in winter 2013, the science team demonstrated that at least one past environment on Mars was habitable by known terrestrial microbes Vaniman et al, 2014). One of the instruments used to characterize this environment was the Mars Hand Lens Imager (MAHLI; Edgett et al, 2012). MAHLI is the highest-resolution camera on the rover, with 13.9 lm/pixel resolution at 2.1 cm working distance (Edgett et al, 2012).…”
Section: Implications For Biosignature Detection With the Mars Curiosmentioning
confidence: 99%
“…One of the instruments used to characterize this environment was the Mars Hand Lens Imager (MAHLI; Edgett et al, 2012). MAHLI is the highest-resolution camera on the rover, with 13.9 lm/pixel resolution at 2.1 cm working distance (Edgett et al, 2012). At this resolution, an object will need to approach 3 pixels in size to appear discernable, and actual precision (discerning the smallest feature) and accuracy (constraining the distribution of features) are subject to additional constraints (Karunatillake et al, 2013).…”
Section: Implications For Biosignature Detection With the Mars Curiosmentioning
confidence: 99%
“…These instruments include the Mast Camera [16], a laser induced breakdown spectrometer for remote elemental composition (ChemCam, [17,18]), a microscopic imager (MAHLI, [19]), an APXS [16], and chemistry and mineralogy by powder x-ray diffraction and x-ray fluorescence (CheMin, [20]), as well as a quadrupole mass spectrometer, a gas chromatograph, and a tunable laser spectrometer (SAM, [21]). This suite of instruments onboard MSL will characterize the martian surface in unprecedented detail, rivaling what can be done in the laboratory on Earth.…”
Section: A In Situ and Remote Sensing Observations Of Mars From Landmentioning
confidence: 99%